From adversity to adaptation: the struggle between resilience and athlete burnout in stressful situations - Cai, Chenyi; Mei, Zhengyang; Yang, Yang; Luo, Shi (Frontiers in Psychology, 2025)
Athlete burnout is considered a negative psychological consequence of stressors in sports, with the potential to adversely affect both the physical and mental well-being of athletes, as well as their overall performance. Resilience serves as a protective factor against stressors, enabling athletes to effectively manage the unique challenges they encounter in the sports environment, ultimately helping protect them from burnout. This narrative review aimed to summarize the direct evidence regarding the relationship between resilience and athlete burnout. By examining existing theories and empirical evidence, the relationship between resilience and athlete burnout was explored and discussed in terms of individual and environmental factors, theoretical models, and neurobiological mechanisms to construct effective intervention programs to prevent and control the occurrence of athlete burnout. At present, resilience can positively influence athlete burnout through individual factors (perceived stress, coping strategies, and motivation) as well as environmental factors (social support, motivational climate, family cohesion, and coach-athlete relationship). The theoretical models mainly include the stress coping process model of athlete resilience and the systematic self-reflection model. These models elucidate the relationship between resilience and athlete burnout from the viewpoints of stress coping and self-reflection, respectively. The neurobiological mechanisms through which resilience influences athlete burnout are explored primarily through the hypothalamic–pituitary–adrenal (HPA) axis and the mesolimbic dopamine system. These mechanisms suggest that resilience has an effect on athlete burnout primarily through stress hormone levels and brain region activity related to reward and motivation. However, the pathways and mechanisms through which resilience influences athlete burnout require further in-depth investigation. Future research should combine the longitudinal perspective to track the dynamic impact relationship between resilience and athlete burnout and focus on examining the relevant theoretical framework from a multidisciplinary research perspective to provide a theoretical basis for coaches and sports managers to formulate scientific training programs. This will help enhance athlete resilience, effectively prevent and mitigate the risk of burnout, and promote the development of athletes’ physical and mental well-being.